Mechanical alloying of iron-coated NbC and Si in stirred media mill - Al-Azzawi A.; Kristály F.; Rácz Á.; Baumli P.; Bohács K.; Mucsi G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the current research, the effect of mechanical alloying (MA) of iron-coated NbC and Si on the material’s fineness and crystal structure was investigated. The MA experiments were carried out in a batch-type laboratory scale stirred media mill for various residence times up to 240 min in isopropanol. During MA, milling energy was measured, and stress energy (SE) was calculated. Morphology and material structural changes, during the mechanical alloying process, were determined by means of scanning electron microscopy (SEM) and powder X-ray diffraction (XRD), respectively. The particle size distribution of the product was measured by a Horiba 950 LA laser particle size analyser. Evolution of phases during highenergy milling of NbC, Al-Fe-carbide, Fe, and Si was studied as a function of specific milling energy. Transformations in the crystal structure were revealed, namely the generation of cementite and Nb-Si-carbide, which was proved by XRD results and thermodynamic calculations. As result of the experiments, optimum MA conditions were determined. The application of the mechanical alloying method gives the opportunity to produce nanocrystalline phase from the initial ironcoated NbC and Si powder